Effects of organic complexed or inorganic Co, Cu, Mn and Zn supplementation during a 45-day preconditioning period on productive and health responses of feeder cattle. (18th May 2017) - Lippolis, K. D.; Cooke, R. F.; Silva, L. G. T.; Schubach, K. M.; Brandao, A. P.; Marques, R. S.; Larson, C. K.; Russell, J. R.; Arispe, S. A.; DelCurto, T.; Bohnert, D. W.
Abstract : This experiment evaluated production and health parameters among cattle offered concentrates containing inorganic or organic complexed sources of supplemental Cu, Co, Mn and Zn during a 45-day preconditioning period. In total, 90 Angus×Hereford calves were weaned at 7 months (day −1), sorted by sex, weaning BW and age (261±2 kg; 224±2 days), and allocated to 18 drylot pens (one heifer and four steers per pen) on day 0; thus, all pens had equivalent initial BW and age. Pens were randomly assigned to receive a corn-based preconditioning concentrate containing: (1) Cu, Co, Mn and Zn sulfate sources (INR), (2) Cu, Mn, Co and Zn complexed organic source (AAC) or (3) no Cu, Co, Mn and Zn supplementation (CON). From day 0 to 45, cattle received concentrate treatments (2.7 kg/animal daily, as-fed basis) and had free-choice access to orchardgrass ( Dactylis glomerata L.), long-stem hay and water. The INR and AAC treatments were formulated to provide the same daily amount of Co, Cu, Mn and Zn at a 50-, 16-, 8- and ninefold increase, respectively, compared with the CON treatment. On day 46, cattle were transported to a commercial feedlot, maintained as a single pen, and offered a free-choice receiving diet until day 103. Calf full BW was recorded on days −1 and 0, 45 and 46, and 102 and 103 for average daily gain (ADG) calculation. Liver biopsy was performed on days 0 (used as covariate), 22 and 45. Cattle were vaccinated against respiratory pathogens on days 15, 29 and 46. Blood samples were collected on days 15, 29, 45, 47, 49, 53 and 60. During preconditioning, mean liver concentrations of Co, Zn and Cu were greater ( P ⩽0.03) in AAC and INR compared with CON. No treatment effects were detected ( P ⩾0.17) for preconditioning feed intake, ADG or feed efficiency. No treatment effects were detected ( P ⩾0.48) for plasma concentrations of antibodies against Mannheimia haemolytica, bovine viral diarrhea types 1 and 2 viruses. Plasma haptoglobin concentrations were similar among treatments ( P =0.98). Mean plasma cortisol concentration was greater ( P ⩽0.04) in CON compared with INR and AAC. No treatment effects were detected ( P ⩾0.37) for cattle ADG during feedlot receiving. Hence, INR and AAC increased liver concentrations of Co, Zn and Cu through preconditioning, but did not impact cattle performance and immunity responses during preconditioning and feedlot receiving.